Horizontal Information Flow: An Exploratory Study - Albaum, Gerald (Academy of Management Journal, 1964)
The article discusses a study which examined the extent to which information, particularly the unsolicited type, flows freely and accurately within a business firm. The experiment was conducted in a highly diversified multi-product electrical manufacturing company which was decentralized along product lines. The study used six items of information that were subsequently transmitted to the company's various units. A discussion is presented about the possible distortion of information found during the process of transmission. The experiment appeared to have value beyond showing how unsolicited information is handled. It indicates that there is not a free flow of unsolicited information within the test company.